The US-China trade war: interrogating globalisation of technology - Nzube A. Chukwuma; Le Minh Ngoc; Previous Mativenga (Cogent Social Sciences)
The US-China trade War in 2018 is one of the 595 documented trade-related disputes reported by the WTO since 1995. Despite the January 2020 agreement between the two countries, the causes of the trade wars appear implicated in international economic relations between the two world economies. In this trade war, the dominant narratives revolve around currency pegging, trade imbalance, intellectual property rights, and most-favoured-nation status as factors propelling the US-China trade war. While these factors have drawn significant attention to scholarly study, they have yet to yield reliable insight into the role of globalisation and technology. With the help of explanatory research design, the study offered an understanding of why the US-China trade war results from the structural changes of economic globalization facilitated by technology diffusion that shift economic growth benefits from the Global North to the Global South with internal structural implications for the US.